Piku [videorecording (DVD)] = Pīkū - Sircar, Shoojit; Bachchan, Amitabh, 1942-; Padukone, Deepika, 1986-; Khan, Irrfan, 1967-2020- (Reliance Home Video & Games, a division of Reliance Big Entertainment, 2015)
A quirky comedy about the relationship between an aging father and his young daughter, living in a cosmopolitan city, dealing with each other's conflicting ideologies while being fully aware that they are each other's only emotional support.